The sleeping giant of Goll - Abbott, Tony, 1952-; Copyright Paperback Collection (Library of Congress) (New York : Scholastic, 2000)
The evil Lord Sparr has used magic to wake up a sleeping giant! Now Eric, Julie, and Neal must join forces with a brave dragon and the Oobja people of Panjibarrh to help save their Droonian friends.
"A Little Apple paperback."
G2
Keywords: Magic -- Juvenile fiction; Magic -- Fiction; Fantasy